Avaliação tridimensional do crescimento da face de crianças com obstrução das vias aéreas superiores após adeno/tonsilectomia - Mariana Maciel Tinano (2017)
Introduction: There are controversies in the literature about the influence of the adenotonsillectomy surgery in craniofacial growth, but due to the inconclusive findings, debates are still frequent on this topic. The use of new three-dimensional (3D) imaging tool and the detailed presentation of a series of clinical cases might contribute to the understanding of this complex relationship. Objective: To evaluate, through a descriptive series of cases, skeletal 3D changes of the face of children with upper airway obstruction submitted to adeno and/or tonsillectomy and, and compare with a group of children who were not submitted to the surgery. Methods: From a universe of 150 patients screened at an outpatient hospital clinic at a referral center for the diagnosis and treatment of mouth breathing in 2014 and 2015, 15 children (age ranging from 4 to 9 years, mean ± 5.42 years) were selected. All of them presented an endoscopic diagnosis of pharyngeal and/or palatine tonsils hypertrophy, polysomnographic diagnosis of obstructive sleep apnea syndrome (OSAS) and indication of tonsillectomy and/or adenoidectomy (T&A) for this prospective study. Eleven of these children were evaluated before surgery (T0), and 18.7 months (ranging from 12 to 30 months) after T&A (T1). Four children were not submitted to T&A because of institutional bureaucratic reasons and served as comparasion individuals during this 18,7 observation months. In both time-points the children underwent ENT clinical examination, flexible nasoendoscopy and computed tomography (CT) examinations. The maxillary and mandibular skeletal changes between (T0) and (T1) were analyzed quantitatively and visually based on 3D surface models. Visual analysis were performed using semi-transparencies and color-coded maps (color-maps), while quantitative assessments were performed using linear and angular measuraments of anatomical frames in (T0) and (T1) and displacement of the measuraments between (T0) and (T1) using software ITK-SNAP and SLICER. Results: In 6 T&A children and in 2 children who were not submitted to the surgery, it was observed the opening of the palatal angle in the maxilla, and the vertical and 3D displacement of the palatal point (P) after surgery. In 9 T&A children and in 3 children who were not submitted to the surgery, there was an increase in the measurement of the length of the mandible (chin to the condyles and posterior symphysis point to the condyles), and inter-condylar growth (C). Condylar growth and dental changes occurred between (T0) and (T1), both in T&A children and in children who were not submitted to T&A, and apparently are associated with the normal growth of individuals. Similar patterns of facial growth were found in mouth breathing patients who were not submitted to T&A during the observation period. Conclusion: The growth of the face of T&A mouth breathing children occurred similar to children who were not submitted to the surgery in general, without changes after adeno and/or tonsillectomy.